Joker: folie à deux [videorecording (Blu-Ray)] - Phillips, Todd, 1970-; Silver, Scott; Phoenix, Joaquin; Lady Gaga; Beetz, Zazie; Gleeson, Brendan; Keener, Catherine; Coogan, Steve; Lawtey, Harry; Gill, Leigh; Leung, Ken; Hildur Guðnadóttir; et al. (Warner Bros., 2024)
Failed comedian Arthur Fleck meets the love of his life, Harley Quinn, while in Arkham State Hospital. Upon release, the pair embark on a doomed romantic misadventure.